THE CORRELATION BETWEEN STUDENTS’ READING HABIT AND THEIR WRITING SKILL - Wahyuni Anggeriyanti (ICoTE Proceedings)
The objective of this research was to clarify the correlation between students’ reading habit and their writing skill to the second semester students of IKIP-PGRI Pontianak. The method used in this research was correlational research method. The sample was chosen by using cluster random sampling and it was from A morning class at English Education Department of IKIP-PGRI Pontianak that consisted of forty four students on the second semester. Subsequently, tools for data collection were closed-questionnaire and written test. According to the findings, the result showed that 0.470 (rxy) > than 0.297 (rtable). If rxy > than rtable, so there was significant correlation. Furthermore, the result of this research implied that reading habit gives the positive effect for students writing skill. From this research, it is recommended for the student to accustom reading so that they will get much information which will be used in their writing skill.